GE_GERICHTE P/10294/2013 vom 8. Juni 2023 - GE Cour de justice (2023)
GESTION DÉLOYALE;COMPLICITÉ;PRÉTENTION DE DROIT PUBLIC;PRINCIPE DE L'ACCUSATION;PRESCRIPTION | CP.158; CP.251; CP.71; CP.98; CPP.9